The Impact of COVID-19 on Neuro-Ophthalmology Office Visits and Adoption of Telemedicine Services. Issue 3 (September 2021) - Moss, Heather E.; Ko, Melissa W.; Mackay, Devin D.; Chauhan, Divya; Gutierrez, Karen G.; Villegas, Natacha C.; Lai, Kevin E.
Abstract : Background: The COVID-19 public health emergency (PHE) has significantly changed medical practice in the United States, including an increase in the utilization of telemedicine. Here, we characterize change in neuro-ophthalmic care delivery during the early COVID-19 PHE, including a comparison of care delivered via telemedicine and in office. Methods: Neuro-ophthalmology outpatient encounters from 3 practices in the United States (4 providers) were studied during the early COVID-19 PHE (March 15, 2020–June 15, 2020) and during the same dates 1 year prior. For unique patient visits, patient demographics, visit types, visit format, and diagnosis were compared between years and between synchronous telehealth and in-office formats for 2020. Results: There were 1, 276 encounters for 1, 167 patients. There were 30% fewer unique patient visits in 2020 vs 2019 (477 vs 670) and 55% fewer in-office visits (299 vs 670). Compared with 2019, encounters in 2020 were more likely to be established, to occur via telemedicine and to relate to an efferent diagnosis. In 2020, synchronous telehealth visits were more likely to be established compared with in-office encounters. Conclusions: In the practices studied, a lower volume of neuro-ophthalmic care was delivered during the early COVID-19 public health emergency than in the same period in 2019. The type of care shifted toward established patients with efferent diagnoses and the modality of care shifted toward telemedicine. Abstract : Supplemental Digital Content is Available in the Text.